METODE PENELITIAN ETNOGRAFI: KONSEP DAN DESAINNYA - Sunaryanto (STAI DI AL-HIKMAH, 2023)
This short paper aims to find a form of ethnographic research design. The focus of the discussion is on types of research, research subjects, types of data, data sources, data collection techniques, and data analysis techniques. The method used in this study is library research. So that all research data is only based on library data, for example journals, books, research results, and relevant websites. The conclusion of this study is that ethnography as a qualitative research method has experienced developments, for example the emergence of audience ethnography, digital ethnography, visual ethnography and others. With this development, ethnographic research designs can be formed and developed according to the research context that will be made by a researcher. Ethnography is research that can be used in various scientific disciplines such as economics, education, politics, communication, etc